2016
DOI: 10.1186/s12967-016-0816-x
|View full text |Cite
|
Sign up to set email alerts
|

Human lung adenocarcinoma cell cultures derived from malignant pleural effusions as model system to predict patients chemosensitivity

Abstract: BackgroundLung cancer is the leading cause of cancer related deaths and Malignant Pleural Effusion (MPE) is a frequent complication. Current therapies suffer from lack of efficacy in a great percentage of cases, especially when cancer is diagnosed at a late stage. Moreover patients’ responses vary and the outcome is unpredictable. Therefore, the identification of patients who will benefit most of chemotherapy treatment is important for accurate prognostication and better outcome. In this study, using malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
1
37
0
2
Order By: Relevance
“…A recent study also showed how KRAS mutations can be missed in MPE samples, but persist in cultured cell lines derived from the same patients16, a finding recapitulated in patients from our centre. To this end, most MPE sequencing studies were performed in Asian populations with high EGFR and EML/ALK and low KRAS mutation frequencies89101112131415163536. A recent study of European patients with resected lung tumours clearly showed that KRAS mutations are linked with pleural spread19.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study also showed how KRAS mutations can be missed in MPE samples, but persist in cultured cell lines derived from the same patients16, a finding recapitulated in patients from our centre. To this end, most MPE sequencing studies were performed in Asian populations with high EGFR and EML/ALK and low KRAS mutation frequencies89101112131415163536. A recent study of European patients with resected lung tumours clearly showed that KRAS mutations are linked with pleural spread19.…”
Section: Discussionsupporting
confidence: 73%
“…These orthotopic PDX models can be used to predict the drug response of the patient tumour. 19,20 However, orthotopic implantation is Genetically engineered mouse models (GEMMs) display specific mutations in somatic cells that underlie human cancer, such as a p53 mutation in lung cells leading to non-small-cell lung cancer. 21,22 This allows study of defined mutations in the development and progression of tumours.…”
Section: Limitations Of Mouse Tumour Modelsmentioning
confidence: 99%
“…Комбинирование методов оценки химиочувствительности по EC50 (концентрация агента, вызывающего ингибирование на 50% роста клеток) первичных культур клеток аденокарциномы из злокачественной плевральной эффузии немелкоклеточного рака легкого при помощи колориметрического WST-1 теста и генотипирования с использованием секвенирования следующего поколения позволяет целенаправленно и индивидуально подобрать химиопрепараты и провести стратификацию пациентов на подгруппы [76].…”
Section: методы оценки химиочувствительности опухолевых клеток с испоunclassified